LESSON LEARNT DARI PROSES PELATIHAN PERENCANAAN KEUANGAN KELUARGA - Hidayah, Nur; Kusmawati, Kusmawati; Rumasukun, Endang; Wahyuna, Wahyuna (Universitas katolik Musi Charitas, 2023)
The problem of households in Brongkendik village is financial difficulty because they do not have a life goal. Several factors influence this, such as marriage customs, baby birth customs,